Sistem Informasi Akuntansi Pada UD. XYZ - Jonathan Audrey Wiselie; Alexander Setiawan; Andy Setiabudi (Jurnal Infra, 2017)
UD. XYZ is a trade company that works in selling furnitures. The trade activity done by UD. XYZ covers retail and wholesale sale (as the stores supplier).  Even though UD. XYZ has financial department that holds the responsibility to company’s financial management, there is only a little data process system usage with Microsoft Excel. To overcome the problem that is faced by UD. XYZ in processing the financial data, then the written chose the tittle “Accounting Information System.”From this background, a structured Accounting Information System that supports the company in doing sale, purchase, sale return, purchase return, debt payment, and credit payment, which is also focused on profit loss calculation on the company is made. The Accounting Information System was made using the programming language such as PHP (Hypertext Preprocessor), HTML (Hyper Text Markup Language), and MYSQL as the database.The designed Accounting Information System for UD. XYZ hopefully can help the company processing transactions into computerized financial report, which includes master report, sale and purchase report, until the output can show the profit loss condition of the company and the balance sheets of every stores owned by UD. XYZ.